2022
DOI: 10.3390/coatings12070935
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bias and Nitrogen Pressure on TiNbN Coatings in Arc-PVD Processes—A Multifactorial Study

Abstract: Titanium-based nitride physical vapour deposition (PVD) coatings, such as titanium nitride (TiN), are state-of-the-art solutions for surface modifications of CoCrMo-based implants for patients who are hypersensitive to metallic ions such as cobalt, chromium and nickel. Variations of the process parameters during the cathodic arc evaporation are known to exhibit an impact on the surface properties of coatings. The aim of this study was to characterise the effect of the substrate bias and the nitrogen pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To reduce the generation of wear particles and metal ion release, the surfaces of metallic endoprostheses can be coated with titanium‐based nitrides like TiNbN 13,32 . This coating can also improve the implant's biocompatibility 3,19,20 . It has been previously reported that osteoblasts proliferate more and release less IL‐6 when cultured on ceramic‐coated implant surfaces than on the bare metal alloy 33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the generation of wear particles and metal ion release, the surfaces of metallic endoprostheses can be coated with titanium‐based nitrides like TiNbN 13,32 . This coating can also improve the implant's biocompatibility 3,19,20 . It has been previously reported that osteoblasts proliferate more and release less IL‐6 when cultured on ceramic‐coated implant surfaces than on the bare metal alloy 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…13,32 This coating can also improve the implant's biocompatibility. 3,19,20 It has been previously reported that osteoblasts proliferate more and release less IL-6 when cultured on ceramic-coated implant surfaces than on the bare metal alloy. 33,34 Since wear can also occur on PVD-coated implants under certain circumstances, 13,27 the biological response of osteoblasts to those coating particles is clinically relevant.…”
Section: Induction Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing nitrogen pressure results in higher deposition rates for the TiN film. It has been shown that the coating thickness increases with increased nitrogen pressure [41].…”
Section: Sem Observation Of the Prepared Samplesmentioning
confidence: 99%
“…Without the comprehensive investigation of the "film/substrate" system, it is often difficult to obtain the optimum performance of the films. While the hardness and the strength of the film are effectively improved, it is necessary to consider the influence of the substrate (or film-substrate compatibility) on the overall durability of the coated alloys, in addition to the effect of the film characteristics (composition, structure, and process change) [10,11] or the wear medium [12].…”
Section: Introductionmentioning
confidence: 99%